Effect of Aerobic Exercise and Yoga on Heart Rate Variability (HRV) Parameters in Young Adults (International Journal of Physiology, 2019)
Analysis of beat-to-beat variability of heart rate(HR) has been stated to represent one of the promising quantitative markers of autonomic activity. Dysregulation of autonomic activity seen in life style associated disease is believed to be modified by physical activity. Present study was to evaluate and compare the autonomic activity in aerobic exercisers and yoga practitioners. Ninety healthy male subjects aged 30–40 years were included in the study. The study consisted of three group with 30 subjects in each. Group1: Subjects who practiced regular structured aerobic exercise for a period of minimum 6 months. Group 2: Subjects practiced yoga regularly for a period of minimum 6 months. Group 3: Healthy subjects (normal BMI) neither practiced yoga or any type of exercise regularly. Heart Rate and HRV were recorded in all subjects using standard procedures. The study showed decreased LF (Low Frequency) in Yoga group and exercise group than control group, also decreased HR, and LF/HF(Low frequency/High Frequency) ratio and increase HR in yoga group. This indicates that parasympathetic activity is substantially greater in yoga practitioners followed by athletes and control.